Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c6nr06983e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of precisely defined DNA nanotube superstructures using DNA origami seeds

Abstract: We demonstrate a versatile process for assembling micron-scale filament architectures by controlling where DNA tile nanotubes nucleate on DNA origami assemblies. "Nunchucks," potential mechanical magnifiers of nanoscale dynamics consisting of two nanotubes connected by a dsDNA linker, form at yields sufficient for application and consistent with models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 24 publications
(29 reference statements)
1
43
0
1
Order By: Relevance
“…DNA cages refer to wireframe architectures assembly from DNA strands (Chen and Seeman, 1991;Wang et al, 2019). Various DNA cages include DNA polyhedrons (Wang et al, 2019) and DNA nanotube (Jorgenson et al, 2017;Mohammed et al, 2017) were reported. DNA polyhedrons represent a 3D cage-like compact structure which is stable and easily absorbed by cells.…”
Section: Wireframe Dna Cagesmentioning
confidence: 99%
“…DNA cages refer to wireframe architectures assembly from DNA strands (Chen and Seeman, 1991;Wang et al, 2019). Various DNA cages include DNA polyhedrons (Wang et al, 2019) and DNA nanotube (Jorgenson et al, 2017;Mohammed et al, 2017) were reported. DNA polyhedrons represent a 3D cage-like compact structure which is stable and easily absorbed by cells.…”
Section: Wireframe Dna Cagesmentioning
confidence: 99%
“…Hierbei zeigten Röhren mit Origami‐Keimen eine wesentlich höhere Wachstumsrate als in unbehandelten Ansätzen . Die Hybridisierung zweier Keime mittels dsDNA‐Verbindungsstück führt zur Bildung von Nanoröhren in Form von “Nunchakus” . Keimbildner mit L‐, T‐ oder Y‐Form erzeugen entsprechende DNA‐Nanoröhren mit einer Länge von 2 oder 3 μm .…”
Section: Design‐strategienunclassified
“…As we all know, Self-Assembly is commonly regarded as an emerging technology which could be used in nano-fabrication or computation because of its nanoscale feature size [1,[7][8][9][10][11]. In nano-manufacture system and algorithmic system, DNA is applied in Self-Assembly as a main technology because of its wonderful versatility.…”
Section: Introductionmentioning
confidence: 99%